The role of net development as a barrier to moisture loss in netted melon fruit (Cucumis melo L.) - Thanidchaya Puthmee (2018)
The transpiration rate of cuticular membrane and fissures that comprise the netting on fruits of three netted melon cultivars, Life, Andesu, and Gurandoru, were measured during fruit development. Fissures in the equatorial region first developed vertically, then became interconnected by horizontal fissures as the fruit developed. Some cracks remained along the net, even at the fruit ripening stage, regardless of cultivar. Both lignified and suberized cell wall layers in the net tissues of the cultivar Life were thinner than those of the other cultivars, probably because of the shorter developmental period of fruits in the variety. Nevertheless, net transpiration rate did not differ significantly among cultivars at the fruit ripening stage. Peroxidase (POD) activity in the skin tissues of 'Life' was lower than that in 'Andesu' and 'Gurandoru' throughout fruit development and was not correlatedwith climacteric ethylene production. Among these cultivars, significantly higher ethylene production occurred in 'Life' fruit at the ripening stage. This can accelerate membrane permeability of hypodermal tissues, resulting in rapid fruit softening. Our results indicate that the net tissues of netted melons can be as waterproof as cutinized membranes if suberized cell wall layers with wax depositions develop below the net fissures at the fruit ripening stage.